2004
DOI: 10.1016/j.catcom.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for the oxidative methylation of benzene with methane over zeolite catalysts

Abstract: We have previously shown in our previous investigations that the presence of oxygen is required for the benzene methylation with methane over zeolite catalysts in a high pressure batch reactor. Thus, a two-step mechanism involving the formation of methanol intermediate by methane partial oxidation followed by benzene methylation with methanol in the second step was postulated. This paper now presents the results of further investigation that provide more evidence that the catalytic benzene methylation with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
4
20
1
1
Order By: Relevance
“…This observation is similar to earlier observation that the presence of small amounts of hydrocarbon additives (especially ethane) lowered the initiation temperatures of partial oxidation of methane to methanol and increased the methanol selectivity and yield (Gesser et al, 1985;Fujimoto, 1994). This observation therefore extends the significance of the oxidative methylation reaction and we had earlier suggested that this avenue could be explored further for optimisation of the conversion of methane to methanol (Adebajo et al, 2004).…”
Section: Relevance Of Oxidative Aromatics Methylation To Methane-to-msupporting
confidence: 77%
See 4 more Smart Citations
“…This observation is similar to earlier observation that the presence of small amounts of hydrocarbon additives (especially ethane) lowered the initiation temperatures of partial oxidation of methane to methanol and increased the methanol selectivity and yield (Gesser et al, 1985;Fujimoto, 1994). This observation therefore extends the significance of the oxidative methylation reaction and we had earlier suggested that this avenue could be explored further for optimisation of the conversion of methane to methanol (Adebajo et al, 2004).…”
Section: Relevance Of Oxidative Aromatics Methylation To Methane-to-msupporting
confidence: 77%
“…The chapter also presents a discussion of the progress that has been made on the development of chemical systems like MMO that are capable of oxidizing methane at ambient conditions. One interesting observation in our previous work on catalytic oxidative methylation of aromatics with methane that is directly relevant to the conversion of methane to methanol is that it is possible to inhibit the complete oxidation of www.intechopen.com methane to carbon dioxide in the presence of an additive (Adebajo et al, 2000;Adebajo et al, 2004). This chapter also provides a brief summary of such oxidative methylation reaction and its significance to methanol conversion.…”
Section: Kmentioning
confidence: 99%
See 3 more Smart Citations